Factors influencing voluntary audit among small and medium enterprises: the Malaysian evidence / Erlane K Ghani, Syakir Munir Ismail Munir and Zuraidah Mohd Zam - Ghani, Erlane K; Ismail Munir, Syakir Munir; Mohd Zam, Zuraidah (Faculty of Accountancy, 2019)
In Malaysia, the Small and Medium Enterprises (SMEs) are encouraged to get their financial statements audited although such practice is on a voluntary basis. This study examines the voluntary practices of the SMEs in getting their financial statements audited. Specifically, this study examines the factors influencing the voluntary audit among the SMES. Three factors are chosen namely, improved quality of financial statements, managerial ownership and managers’ perception towards voluntary audit. Using questionnaire as the research instrument on 70 SMEs, the results show that managerial ownership and managers’ perception towards voluntary audit influence the SMEs to get their financial statements audited. On the other hand, the results show that there is a negative relationship of the improvement quality of financial statement towards voluntary audit among the SMEs. The findings of this study provide further understanding on the SMEs’ action in willingness to adopt one practice. In addition, this study also provides valuable information to the Malaysian regulatory and professional accounting bodies in their debates on providing audit exemption for the SMEs in Malaysia.